2021
DOI: 10.1177/1049909120986800
|View full text |Cite
|
Sign up to set email alerts
|

Cost Savings Associated With Palliative Care Among Older Adults With Advanced Cancer

Abstract: Background: There is inconsistent evidence that palliative care intervention decreases total healthcare expenditure at end-of-life for oncology patients. This inconsistent evidence may result from small sample sizes at single institution studies and disparate characterization of costs across studies. Comprehensive studies in population-based datasets are needed to fully understand the impact of palliative care on total healthcare costs. This study analyzed the impact of palliative care on total healthcare cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Health policymakers must learn to promote access to the service which may reduce unnecessary interventions at 'patients' end of life. Other studies also suggested palliative care reduces healthcare cost for seriously ill lung cancer patients [ 15 , 28 30 ]. However, the datasets of those studies were limited to certain population groups.…”
Section: Discussionmentioning
confidence: 99%
“…Health policymakers must learn to promote access to the service which may reduce unnecessary interventions at 'patients' end of life. Other studies also suggested palliative care reduces healthcare cost for seriously ill lung cancer patients [ 15 , 28 30 ]. However, the datasets of those studies were limited to certain population groups.…”
Section: Discussionmentioning
confidence: 99%
“…7,21,31 However, they refer to the cancer population, and focus on reducing hospital stays, days in the ICU, or use of chemotherapy. 39,40 This study included both oncological and non-oncological patients, focusing on the last hospital admission of patients dying in the hospital, showing that savings with PC teams were due to the more appropriate use of hospital resources. Similarly, certain studies show economic benefits with better cost efficiency in non-cancer patients seen by PC teams, but they have again focused on overall reduction of admission costs and not on a cost analysis according to the resources used, as performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Este estudio demuestra que los cuidados paliativos tienen la capacidad de reducir sustancialmente el gasto sanitario entre los pacientes con cáncer avanzado. La consulta temprana de cuidados paliativos da lugar a mayores reducciones de costes que la consulta en la última semana de vida (Sheridan et al, 2021).…”
Section: Fuenteunclassified